PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SD MUHAMMADIYAH 10 PALEMBANG (JS (JURNAL SEKOLAH), 2022)
Abstract : The effect of the Numbered Head Together learning model on mathematics learning outcomes of Students in class III SD Muhammadiyah 10 Palembang. The purpose of this study was to determine whether there was an effect of the Numbered Head Together learning model on the mathematics learning outcomes of third grade students at SD Muhammadiyah 10 Palembang. This type of research is quantitative by using the type of research Quasi Experimental Design with the form of design used in this study is the Nonequivalent Control Group Design. The sampling technique used is the total sample technique. In the final analysis of the calculation using the paired sample t-test hypothesis test, the data obtained a significant value (2-tailed) 0.000